AODTU-002 Per oral endoscopic myotomy: updated results from a uk case series. (17th June 2017) - Gulati, S; Emmanuel, A; Inoue, H; Haji, A; Hayee, B
Abstract : Introduction: Per-oral endoscopic myotomy (POEM) has been adopted as a minimally invasive treatment option for achalasia and even spastic oesophageal conditions. The first case of POEM was performed at the King's Institute of Therapeutic Endoscopy (KITE) in 2013. Here we present our updated UK case series including the first UK case of diffuse oesophageal spasm (DES). Method: Prospective data was collected for consecutive patients undergoing POEM including demographics, technique, use of Endoluminal Functional Lumen Imaging Probe (EndoFLIP) and adverse events. Clinical success was defined as a reduction of Eckardt score (ES) to ≤2 or by 4 points. Follow up data at 3 and 12–24 months (m) post-POEM was analysed using the Wilcoxon signed ranks test to compare pre- and post-POEM ES, 4sIRP and pre and post-treatment GORD-HRQoL score. Repeated-measures ANOVA was used for multiple time-point comparisons. Results: POEM was performed in 51 patients (22F, age 48.6+/-13.5 years). Median gastric and oesophageal myotomy was 3 cm (2-4) and 10(3-18) respectively with selective circular myotomy in all cases and posterior approach in 11. POEM was clinically successful in n=41/44 (93%) eligible for review at 3m. Reduction in ES at 3m; 8.5 (5–12) vs 0 (0–6) p<0.0001 was sustained in 30 patients with median follow up of 15m (3-36);2 (0–7) ANOVA p<0.0001. IRP-4s reduced 26.43+/-9.81 mmHg vs 8.72+/-5.05 mmHg (p<0.001). Revision of POEM was performed in n=3 at 6, 16 and 27m with clinical success achieved in all cases at 3m review. Pre and post-myotomy EndoFLIP showed an increase in oesophago-gastric junction diameter from 5.87 to 11.27.27 mm(p<0.001) (n=11) and distensibility improved from 1.14 to 2.87 mm 2 /mmHg (p=0.008) (n=8). Median post-POEM GORD-HRQoL score (n=41) was 1 (0–31). 8 patients with scores>12 improved with conservative treatment; 15.5 (13–31) vs 6.5 (1–11, p=0.0078) as did 5 cases of acid reflux identified by 24 hr pH testing in n=19 at time of analysis. Endoclip displacement was encountered in n=2 and replaced endoscopically including readmission of 1 patient for delayed mucosal incision site healing (Clavien-Dindo Grade IIIb). There were no cases of mortality, perforation, infection/major bleeding. Conclusion: This is the largest UK case series of POEM for achalasia including the first successful UK POEM procedure for DES. At our institute, POEM was performed successfully in a potentially more challenging cohort where 52.9% had prior treatment. Our results are in line with international consortia and ASGE 1 findings that POEM is a safe and efficacious procedure for the treatment of achalasia and oesophageal spastic disorders for both short term and sustained symptomatic benefit. Reference: . Stavropoulos S, Desilets D, Fuchs KHet al; Per-oral endoscopic myotomy white paper summary; Gastrointestinal Endoscopy; 2014;1:1–15 Disclosure of Interest: None Declared